The impact of green technology, environmental tax and natural resources on energy efficiency and productivity: Perspective of OECD Rule of Law - Rizwana Yasmeen; Xuhui Zhang; Rui Tao; Wasi Ul Hassan Shah (Energy Reports, 2023)
OECD countries are at the forefront of sustainable development and working in several domains, including energy efficiency, environmental taxes, and the development of green technology. On this premise, the study’s main objective is to examine the impact of green technology , environmental taxes and natural resources on energy efficiency. The study used three dimensions of energy measurement: (i) energy efficiency, (ii) energy productivity, and (iii) energy intensity for OECD. An important feature of the study is the use of the “Rule of Law” to implement tax reforms and green technology. Malmquist–Luenberger and the super SBM-DEA are used to measure energy efficiency and productivity. France, Greece, Italy, Luxemburg, Sweden, Lithuania, Colombia, and Turkey’s energy efficiency range is between 1–1.5. Switzerland’s energy efficiency ranges from 1.5–2.0. The United States of America, Japan, the UK, Australia, Germany, Canada, and South Korea’s energy efficiency ranges are between 0.5–1.0. Beyond that, the higher energy-intensive countries are Canada, Estonia, South Korea, Finland, the USA, the Czech Republic, Australia, and the Slovak Republic. Regression analysis highlighted that the environmental tax and green technology are important drivers for improving energy efficiency and productivity and lowering energy intensity. The impact strength of environmental tax is higher than green technology to boost energy efficiency and limit energy intensity. Increasing rent on natural resources can raise the energy intensity and affects environmental sustainability. The study found that “the rule of law” is important for putting green technologies and tax reform into practice. Due to “the rule of law”, industries must abide by the green principle and pay attention to growth and the environment.